Non-state threats and future wars - Bunker, Robert J. (Frank Cass, 2003)
The intent behind this book was to bring together a team of defence and national security scholars and real-world military and law enforcement operators to focus on the topic of ""Non-State Threats and Future Wars"". The book is divided into four main sections: The first concerns theory. The second section concerns non-state threats and case studies, providing an overview of non-state threats ranging from organized crime networks to cartels, gangs and warlords. The third section is based on counter-OPFOR (opposing force) strategies which detail advanced concepts, urban battlespace environmenta.